An integrated approach for techno-economic and environmental analysis of power generation from paddy residue in Malaysia / Shafini Mohd Shafie - Shafini, Mohd Shafie (2015)
Malaysia is blessed with abundant biomass residue that can potentially be used as a source of electricity generation. One of them is paddy residues. Annually about 3.66 million tonne of paddy residue is left in the fields. Towards year 2020 this value is forecasted to increase to 7 million tonne per year due to emerging technology development in agriculture industries. Paddy residue can potentially be used as feedstock fuel for electricity generation in Malaysia. However, the techno-economic study on paddy residue based power generation for Malaysia condition is still limited. Therefore, this thesis explores the non-technical aspect regarding the potential in using paddy residue, rice husk and rice straw in power generation. In particular LCA (Life Cycle Analysis) and three dimensional integrated economic, energy and environment was employed. The paddy residue can potentially contribute about 2.26% to the total Malaysia’s electricity generated in 2013. The evaluation of rice husk and rice straw based power generation was compared with coal and natural gas electricity generation. Paddy residue power plants not only could solve the problem of removing rice straw from fields without open burning, but also could reduce GHG emissions that contribute to climate change, acidification, and eutrophication, among other environmental problems. The GHG emission saving from coal based electricity generation is 1790 g CO2-Eq / kWh and 1050 g CO2-Eq / kWh for natural gas power generation. This study had also focussed on paddy residue co-firing at existing coal power plant in Malaysia. The investigation covered the aspects of economic, environmental impact and energy. Co-firing paddy residue with coal power plant become most attractive study due to availability of biomass feedstock, reduce dependency on fossil fuel and GHG emission. Analysis of GHG emissions and energy consumption throughout the entire co-firing paddy residue life cycle was based on selected coal power plant capacity output. This thesis also analyses the implication of paddy residue use under different co-fired ratios,transportation systems and CO2 emission prices. The reduction of GHG emissions was found to be significant even at a lower co-firing ratio. This study evaluates the economic feasibility of rice straw life cycle in electricity generation starting with rice straw collection to electricity generation in Malaysia. For an assumption of 20 years, the cost of electricity generated (COE) are between RM 0.72 / kWh to RM 0.53 / kWh for 20 MW to 500 MW respectively. Considering the COE and fuel cost parameters the optimum design can be achieved with plant capacity 150 MW. A sensitivity analysis on financial feasibility shows that the most influences parameter to the NPV is the sale price. Therefore, this study serves as guideline for further investigation on paddy residue based power generation and helps the policy maker, industrial and financial sector in making the decision for understanding the pro and contra of its implementation in Malaysia.